Manufacturing capacity building baseline survey on Small to Medium Enterprises (SME’s) : A case study of Hire Engineering Co. in Zimbabw (International Journal of Engineering and Computer Science, 2013)
This study was undertaken to investigate the aspects to be considered in coming up with manufacturing capacity building baseline for Small to Medium Enterprises (SMEs) firms in the engineering production field. The various competencies, skills and framework required has been highlighted for possible meaningful production of this sector. The enhancing industry policy to spearhead this has been suggested to grow such businesses from the equipment provision and operational point of view.